Sustainable Development : The UN Millennium Development Goals, the UN Global Compact, and the Common Good - Williams, Oliver F. (Book collections on Project MUSE., 2014)
"For business to flourish, society must flourish. In today's global economy, business serves the common good not only by producing goods and services but also by reaching out to the many who are not even in the market because they lack marketable skills and the resources to acquire them. Sustainable Development: The UN Millennium Development Goals, the UN Global Compact, and the Common Good contains twenty-two essays that document the work of Western companies, working through the UN Global Compact and its Principles of Responsible Investment and the Principles for Responsible Management Education, to shape more peaceful and just societies. Seven case studies by leading businesses and private-public partnerships--including Microsoft, Merck, Sumitomo Chemical, Nestle, Coca-Cola, Novartis, and Levi Strauss--outline their projects, especially those advancing the MDGs (Millennium Development Goals) designed to alleviate dire poverty. Twelve chapters reflect on some of the conceptual issues involved with the MDGs, and the three concluding essays examine the future of the UN Global Compact, of the Millennium Development Goals, and of the role of business enterprise in society."--Publisher's Website.